Pharmaco-Optogenetic Targeting of TRPC Activity Allows for Precise Control Over Mast Cell NFAT Signaling - Bacsa, Bernadett; Graziani, Annarita; Krivic, Denis; Wiedner, Patrick; Malli, Roland; Rauter, Thomas; Tiapko, Oleksandra; Groschner, Klaus (Frontiers in Immunology, 2020)
Canonical transient receptor potential (TRPC) channels are considered as elements of the immune cell Ca2+ handling machinery. We therefore hypothesized that TRPC photopharmacology may enable uniquely specific modulation of immune responses. Utilizing a recently established TRPC3/6/7 selective, photochromic benzimidazole agonist OptoBI-1, we set out to test this concept for mast cell NFAT signaling. RBL-2H3 mast cells were found to express TRPC3 and TRPC7 mRNA but lacked appreciable Ca2+/NFAT signaling in response to OptoBI-1 photocycling. Genetic modification of the cells by introduction of single recombinant TRPC isoforms revealed that exclusively TRPC6 expression generated OptoBI sensitivity suitable for opto-chemical control of NFAT1 activity. Expression of any of three benzimidazole-sensitive TRPC isoforms (TRPC3/6/7) reconstituted plasma membrane TRPC conductances in RBL cells, and expression of TRPC6 or TRPC7 enabled light-mediated generation of temporally defined Ca2+ signaling patterns. Nonetheless, only cells overexpressing TRPC6 retained essentially low basal levels of NFAT activity and displayed rapid and efficient NFAT nuclear translocation upon OptoBI-1 photocycling. Hence, genetic modification of the mast cells TRPC expression pattern by the introduction of TRPC6 enables highly specific opto-chemical control over Ca2+ transcription coupling in these immune cells.